Improvement Of Nutritional Status Of Children Age 3-5 Years Through Giving Additional Food Of Dangke Chips - I Kade Wijaya; Mikawati (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2021)
Nutrition problem is essentially a public health problem. Various efforts to improve nutrition have been made, one of which is by providing nutritious and preferred supplementary food for children. The purpose of this study was to examine the increase in the nutritional status of children through the provision of additional food for dangke chips to children aged 3-5 years in the working area of ​​Puskesmas Tamamaung Makassar. This research method is a Quasi-experimental one group pre-post test design, the method of taking the sample in this study is non-probability sampling with convenience sampling technique and the number of samples is 9 respondents. Dangke chips were given for 4 weeks and followed up every 2 weeks to evaluate the improvement in nutritional status. There were differences score?in the nutritional status of children under five before and after giving dangke chips with the Z-Score indicator BW / U week I (p = 0.003), week II (p = 0.001). Giving Dangke Chips for 4 weeks can improve nutritional status based on weight / age. It is advisable for parents to find alternatives to provide additional nutritious food that is preferred by the child to fulfill the nutritional status of the child